Epidemiology of childhood pneumonia in the era of antiretroviral therapy and bacterial conjugate vaccines - Moore, David Paul (My University, 2018)
Background, Pneumonia is the leading non-neonatal cause of under-5 death globally, and in South Africa. Human immunodeﬁciency type 1 (HIV)-infection and -exposure are risk factors for pneumonia in children. Aim We appraised the aetiology of under-5 pneumonia in the era of access to bacterial conjug ate vaccines targeting Haemophilus inﬂuenzae type b and Streptococcus pneumoniae and well functioning prevention of mother-to-child transmission and antiretroviral treatment (ART) programmes to prevent and treat paediatric HIV infection. Methods, This research was conducted within the framework of the Pneumonia Etiology Research for Child Health (PERCH) study, at the South African PERCH site (Chris Hani Baragwanath Academic Hospital, Soweto, Gauteng Province). Cases, aged 1-59 months hospitalised with World Health Organization-deﬁned severe or very severe pneumonia (according to pre-2012 deﬁnitions) from mid-August 2011 through end-August 2013 were compared to age-frequency, HIV-status matched controls. The aetiologic fraction of pneumonia attributed to each potential pathogen was calculated through comparison of nasopharyngeal-oropharyngeal (NP/OP) swab and whole blood PCR results, using conditional logistic regression. Results' Pneumonia incidence (per 100 000 children) was 1 755.00 (95% CI, 1 701.8 to 1 809.5) overall, highest in younger children, HIV-infected and HIV-exposed, uninfected (HEU) children. Respiratory viruses contributed 0.59 (95% CI, 0.47-0.62) of the ‘fraction of association’ (FA) with radiologically-conﬁrmed pneumonia, whereas bacteria were associated with 0.29 (95% CI, 0.18-0.35) in the cohort. Respiratory viruses predominated in HEU (FA 0.53; 95% CI, 0.39-0.58) and HIV-unexposed children (FA 0.57; 95% CI, 0.43-0.61). Opportunistic pathogens (human cytomegalovirus (CMV) and Pneumocystis jirovecii) were the predominant organisms in HIV-infected children (FA 0.58; 95% CI, 0.38-0.65). Respiratory syncytial virus (RSV) was the most important organism associated with case-status in HIV-uninfected children (FA 0.31; 95% CI, 0.30-0.32) and HIV-infected children on ART (FA 0.21; 95% CI, 0.16-0.21). CMV, P. jirovecii and Klebsiella spp. were identiﬁed as being the pathogens most frequently associated with death in children that underwent lung biopsy. Conclusion, Strategies to shorten antibiotic therapy in HIV-uninfected children hospitalised with pneumonia may enhance antibiotic stewardship at the study site. Continued eﬀorts at expediting initiation onto ART in HIV-infected children would likely impact favourably on the burden of opportunistic infection-associated pneumonia and its attendant mortality. Research into vaccination against RSV and CMV is a priority.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulﬁllment of the requirements for the degree of Doctor of Philosophy in the branch of Medicine, Johannesburg, 2018